Graphene Oxide/Carbon Nanotube Composite Hydrogels—Versatile Materials for Microbial Fuel Cell Applications. Issue 21 (16th September 2014) - kumar, G. Gnana; Hashmi, Saud; Karthikeyan, Chandrasekaran; GhavamiNejad, Amin; Vatankhah‐Varnoosfaderani, Mohammad; Stadler, Florian J.
<x xml:space="preserve">Abstract</x> Carbonaceous nanocomposite hydrogels are prepared with an aid of a suspension polymerization method and are used as anodes in microbial fuel cells (MFCs). (Poly N‐Isopropylacrylamide) (PNIPAM) hydrogels filled with electrically conductive carbonaceous nanomaterials exhibit significantly higher MFC efficiencies than the unfilled hydrogel. The observed morphological images clearly show the homogeneous dispersion of carbon nanotubes (CNTs) and graphene oxide (GO) in the PNIPAM matrix. The complex formation of CNTs and GO with NIPAM is evidenced from the structural characterizations. The effectual MFC performances are influenced by combining the materials of interest (GO and CNTs) and are attributed to the high surface area, number of active sites, and improved electron‐transfer processes. The obtained higher MFC efficiencies associated with an excellent durability of the prepared hydrogels open up new possibilities for MFC anode applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>